Automated processing and analysis of medical images based on machine learning - Kutzhan, S.D.; Keldibekova, A.B. (Karagandy University of the name of academician E.A. Buketov, 2025)
This study examines the current challenges in processing and analyzing medical images using machine learning techniques. Based on the Pediatric Chest X-ray Pneumonia dataset, a convolutional neural network (CNN) model was developed and evaluated for its ability to detect pneumonia. The results confirmed the high efficiency of deep learning in medical diagnostics.
Keywords: machine learning; CNN; pneumonia; X-ray; Classification Report; diagnostics